Real-world research of advanced NSCLC immunotherapy based on iRECIST criteria - CHEN Mingjing; YANG Qiao; XU Zihan; LI Feng; YANG Guangrong; YOU Qi; YU Yongxin; SUN Jianguo (Di-san junyi daxue xuebao, 2020)
Objective To analyze the real-world data about immune checkpoint inhibitors (ICIs) for advanced non-small cell lung cancer (NSCLC) based on the modified RECIST 1.1 for immune based therapeutics (iRECIST). Methods According to real-world research methods, all advanced NSCLC patients treated with immune checkpoint inhibitors (ICIs) in our hospital from August 10, 2016 to July 10, 2019 were enrolled in this study. The efficacy, including best overall response (bOR), progression-free survival (PFS) and duration of response (DoR) was evaluated in first-line monotherapy, first-line combination, second-line monotherapy and second-line combination based on iRECIST. Also, immune-related adverse events (irAEs) were evaluated. Results A total of 61 patients (54 males and 7 females) with stage IV NSCLC were included, at a median age of 58 years, and there were 31 cases of adenocarcinoma and 30 cases of squamous carcinoma. The bOR and mPFS were 27.3% and 11.8 months, respectively, for first-line monotherapy; 47.1% and not reached (NR), respectively, for first-line combination, and 35.9% and 11.8 months, respectively, for first-line totally. And the bOR and mPFS were 30% and 6.0 months, respectively, for the second-line monotherapy; were 41.7% and NR, respectively, for second-line combination; and were 36.4% and 6.3 months, respectively for second-line totally. The most common irAEs was grade 1~2 skin toxicity (5 cases, 8.2%). Conclusion Our results show that bOR and PFS of first-line monotherapy, first-line combination, second-line monotherapy are better than the results of previous RCT, and bOR and PFS of second-line combination are significantly better than second-line monotherapy. irAEs are controllable study.